2008
DOI: 10.7705/biomedica.v28i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de prescripción de antirretrovirales en 997 pacientes colombianos

Abstract: Introducción. El tratamiento antirretroviral de la infección por virus de inmunodeficiencia humana ha mejorado la supervivencia y la calidad de vida de los pacientes desde el advenimiento de la terapia combinada en 1996. Objetivos. Conocer el manejo farmacológico de la infección por VIH/sida. Materiales y métodos. Estudio descriptivo observacional con selección de pacientes con infección por VIH/sida, de ambos sexos, de todas las edades, en tratamiento, al menos, durante tres meses (julio a septiembre de 2006)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
4
0
2
Order By: Relevance
“…The increased risk of uncontrolled HIV is associated with the inability to suppress viral load, which leads to resistance and treatment failure (22). The usage frequency of the various antiretroviral drugs and treatment regimens is similar to that reported by previous research (18,23). The present study also confirmed the previously-assessed effectiveness of the HAART guidelines, which state that all patients should receive drugs with high intrinsic value, the appropriate DDD, and effective combinations.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The increased risk of uncontrolled HIV is associated with the inability to suppress viral load, which leads to resistance and treatment failure (22). The usage frequency of the various antiretroviral drugs and treatment regimens is similar to that reported by previous research (18,23). The present study also confirmed the previously-assessed effectiveness of the HAART guidelines, which state that all patients should receive drugs with high intrinsic value, the appropriate DDD, and effective combinations.…”
Section: Discussionsupporting
confidence: 88%
“…No association was found between the virological control of HIV infection and the following variables: age, gender, marital status, history of opportunistic diseases, number of daily dosing intervals, number of STDs acquired, intolerance to drugs, number of drugs, comorbidity management, or number of hospitalizations, contrary to the findings of others (17,18,29). However, a significant association was found between poor control of viral load and each of the following: reporting of non-adherence to treatment, therapeutic failure, number of pills daily, report of anxiety or depression, and the city where the patient was being treated, as established by other studies (17,18,23,29,30).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…En este caso, la causalidad de la reacción adversa fue probable (5 puntos, algoritmo de Naranjo y cols) 15 . Por su parte, los efectos indeseables más frecuentes o eventos adversos, pero sin interrupción del tratamiento 50.588,0 (14.261-168.962) 0 (0-137) 0 (0-47) 0 (0-0) ≤ 40 copias, n (%) a 0 (0,0) 0 (0,0) 20 (57,1) 23 (67,7) 24 (80,0) ≤ 50 copias, n (%) a 0 (0,0) 0 (0,0) 20 (57,1) 24 (80,0) 25 (83,0) 41-400 copias, n (%) 0 (0,0) 0 (0,0) 13 (37,1) 11 (32,3) 6 (20,0) 401-1.000 copias, n (%) 0 (0,0) 0 (0,0) 2 (5,7) 0 (0,0) 0 (0,0) 1.001-10.000 copias, n (%) 7 (17,5) 5 (16,7) 0 (0,0) 0 (0,0) 0 (0,0) 10.001-1.000.000 copias, n (%) 33 (82,5) 25 (83,3) 0 (0,0) 0 (0,0) 0 (0,0) (moderados o leves), fueron: erupción cutánea, síndrome metabólico, pesadillas y mareo en cuatro (13%), tres (10%), dos (7%) y en un paciente (3%), respectivamente. Durante los 12 meses de seguimiento no hubo cambios relevantes en la función hepática, renal o hematológica en los pacientes (Tabla 3).…”
Section: Seguridad Del Esquema Genérico Tdf/3tc/efvunclassified
“…El logro de estos objetivos está determinado por la disponibilidad, acceso y adherencia al TARc 3 . Además, se estima que 64% de los costos de la atención a estos pacientes es generado por los medicamentos 4 y que 20 a 40% de los pacientes que inician TARc no alcanzan las metas terapéuticas de supresión viral, entre otras causas, por el costo de los medicamentos 3,5 .…”
unclassified